Fishing gear technology to mitigate harbour porpoise and seabird bycatch in the Baltic Sea: Gillnet modifications and alternative fishing gear fish pot - Chladek, Jérôme Christophe (Fisheries Research, 2022)
Gillnets are the main fishing gear for small scale fisheries (SSF) globally. They are affordable, easy to use, have a well-adjustable size selectivity and most importantly a high catch efficiency for their target species. In recent times, they are increasingly criticized for resulting in a significant amount of bycaught marine mammals, diving seabirds, and turtles, threatening many of those megafauna species. Gillnets have the highest bycatch intensity of all fishing gears for these taxa. In the Baltic Sea, gillnet fishing is used to fish i.a. cod (Gadus morhua), herring (Clupea harengus), turbot (Scophthalmus maximus), and plaice (Pleuronecta platessa). It causes considerable bycatch of harbour porpoises (Phocoena phocoena) and one the highest gillnet bycatch rates worldwide for diving seabirds in that sea basin. Several of these bird species and one of the two harbour porpoise sub-populations are classed as endangered and considered particularly threatened by gillnet bycatch. Baltic European Union Member States have legal obligations to mitigate the bycatch of these species. This thesis focusses on bycatch mitigation approaches for the Baltic Sea. It starts from the assumption that gillnet bycatch is not solvable by one single technical solution. Rather, a “toolbox" of different measures is required. In line with the toolbox thinking, the thesis took a two-pronged approach: In Part A, an acoustic device for mitigating western Baltic harbour porpoise bycatch in gillnet fishing was tested. In Part B, several alternative gears to gillnets were assessed through a literature review and discussions with gear technologists and fishers. Fish pots were identified as the most suited alternative for Baltic SSF. Cod pots (fish pots for targeting cod) were then developed further to increase their catch efficiency. In Part A (Paper I), an improvement of the cetacean bycatch reduction technology pinger (acoustic deterrent devices attached to gillnets), the “Porpoise ALert” (now marketed as “porpoise-PAL” by manufacturer F3 ...